Horticultural Crops - Kossi Baimey, Hugues; Hamamouch, Noureddine; Adjiguita Kolombia, Yao (IntechOpen, 2020)
Horticultural crops are important for human nutrition. To guarantee successful cultivation for quality and quantity yield, proper identification of pests and diseases, as well as abiotic factors undermining their production, is essential. This ten-chapter textbook describes fungi, bacteria, insects, and nematodes as important issues in horticulture. It documents their epidemiology and management strategies such as genetics and botanical and biological control used for their management. This comprehensive resource is essential for students and researchers of plant genetics, pathology, entomology, and nematology.